2009
DOI: 10.1039/b816593a
|View full text |Cite
|
Sign up to set email alerts
|

Solar disinfection of drinking water (SODIS): an investigation of the effect of UV-A dose on inactivation efficiency

Abstract: The effect of solar UV-A irradiance and solar UV-A dose on the inactivation of Escherichia coli K-12 using solar disinfection (SODIS) was studied. E. coli K-12 was seeded in natural well-water contained in borosilicate glass tubes and exposed to sunlight at different irradiances and doses of solar UV radiation. In addition, E. coli K-12 was also inoculated into poly(ethylene) terephthalate (PET) bottles and in a continuous flow system (10 L min(-1)) to determine the effect of an interrupted and uninterrupted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 15 publications
11
91
1
1
Order By: Relevance
“…These findings contradict the existing literature in drinking water, where the same dose had better effects at higher intensities (Ubomba-Jaswa et al, 2009;Ndounla et al, 2014). The most probable cause for these results, is the discontinuous manner of delivery of light in field applications.…”
Section: Irradiance Effects On Solar Wastewater Disinfectioncontrasting
confidence: 57%
“…These findings contradict the existing literature in drinking water, where the same dose had better effects at higher intensities (Ubomba-Jaswa et al, 2009;Ndounla et al, 2014). The most probable cause for these results, is the discontinuous manner of delivery of light in field applications.…”
Section: Irradiance Effects On Solar Wastewater Disinfectioncontrasting
confidence: 57%
“…Increasing intensity continued to decrease the shoulder length, to a minimum of approximately 80 min, followed by acute log-linear decrease within the next 60 min after the shoulder is finished. In this case, the equilibrium set between the growth forces and the disinfecting action of light is imbalanced against E. coli very fast, indicating a possible minimum dose required for initiating the log-linear decay phase, as also suggested by Sichel et al [22] and Ubomba-Jaswa et al [5]. In total, increasing the intensity from 500 to 1600 W/m 2 has inflicted dramatic change to the necessary exposure time, with the initial 420 min being reduced to (approximately) 130 min, which equals to 70% less time necessary.…”
Section: Resultsmentioning
confidence: 54%
“…However, the coincidence of ample solar supplies in these areas favored studies on solar purification of drinking water sources [3][4][5]. A fair share of SODIS works, reviewed by McGuigan et al [6] have demonstrated the ability of UVA and UVB wavelengths of the solar spectrum to inactivate a vast number of microorganisms, such as Escherichia coli, Salmonella, Shigella Flexneri, Fusarium and more [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a notion of the post-irradiation regrowth was present in some of the previous works, as well, searching for the necessary dose (Ubomba-Jaswa et al, 2009;McGuigan et al, 2012) or exposure time, according to the respective irradiation intensities (Rincon and Pulgarin, 2004b). …”
Section: Introductionmentioning
confidence: 99%
“…A major application of photochemistry/photobiology, which has been extensively studied and recently reviewed (McGuigan et al, 2012) is the solar disinfection of water. This practice has drawn interest among other disinfection methods in developing countries, because of its simplicity and high acceptance rates (Ubomba-Jaswa et al, 2009;McGuigan et al, 2012). Following its introduction, more sophisticated aspects were gradually studied, such as the responses of different microorganisms and solar light delivery methods (continuous-intermittent) (Rincon and Pulgarin, 2003;Sichel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%